2019
DOI: 10.1002/smll.201900455
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Sensing in a Physiological‐Like Cell Niche Using Fluorescent Nanodiamonds Embedded in Electrospun Polymer Nanofibers

Abstract: Fluorescent nanodiamonds (fNDs) containing nitrogen vacancy (NV) centers are promising candidates for quantum sensing in biological environments. This work describes the fabrication and implementation of electrospun poly lactic‐co‐glycolic acid (PLGA) nanofibers embedded with fNDs for optical quantum sensing in an environment, which recapitulates the nanoscale architecture and topography of the cell niche. A protocol that produces uniformly dispersed fNDs within electrospun nanofibers is demonstrated and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
(63 reference statements)
0
31
0
Order By: Relevance
“…16 Detection of magnetic noise using relaxometry has been demonstrated for a range of paramagnetic species, including ferritin, [17][18][19][20] gadolinium, 16,[21][22][23][24][25] manganese ions, 20,26 and superparamagnetic nanoparticles 27 with the possibility of ND-based sensing inside living cells. 28 This method has high sensitivity, as evidenced by the detection of a few ferritin molecules 17 or approximately 5 gadolinium spins per Hz 1/2 in a model biological environment. 22 Recently, relaxometry has been shown useful for pH sensing, 29 and the T1 protocol has been enhanced to take into account ionization and recharging of the NV centers.…”
mentioning
confidence: 99%
“…16 Detection of magnetic noise using relaxometry has been demonstrated for a range of paramagnetic species, including ferritin, [17][18][19][20] gadolinium, 16,[21][22][23][24][25] manganese ions, 20,26 and superparamagnetic nanoparticles 27 with the possibility of ND-based sensing inside living cells. 28 This method has high sensitivity, as evidenced by the detection of a few ferritin molecules 17 or approximately 5 gadolinium spins per Hz 1/2 in a model biological environment. 22 Recently, relaxometry has been shown useful for pH sensing, 29 and the T1 protocol has been enhanced to take into account ionization and recharging of the NV centers.…”
mentioning
confidence: 99%
“…After determining neuronal nontoxicity, they applied spin-based thermometry using the CW-ODMR method and confirmed that the intracellular temperature varied by −1.36°C under a global temperature change of −2.1°C. There is another report on the formation of neural networks from a cul-ture of live differentiated neural stem cells with the help of tissue engineering technology, namely the synthetic scaffolds of electrospun polymer nanofibres incorporating NDs [228]. Furthermore, these experiments can be extended to tissue slices on multielectrode arrays in combination with thermal stimuli [229,230].…”
Section: Temperature Probing For Regenerative Medicine and Pharmacolo...mentioning
confidence: 99%
“…Opening up further applications, fluorescent nanodiamonds were recently combined with biomimetic substrates used in the laboratory. ODMR spectra were obtained from live differentiated neural stem cells functioning as a connected neural network grown on fluorescent nanodiamond embedded nanofibers [250]. See [245] and references therein for a detailed review on the use of nanodiamonds in cells.…”
Section: Biosensitive Measurements a Magnetometry At The Cellular Levelmentioning
confidence: 99%